Decomposition and Nutrient Release Pattern of Leaf Litters of Mangium (Acacia mangium Willd.) - Kumar, K. Gopi; Hegde, R.; Babu, Luckins C. (Indian Journal of Agroforestry, 2020)
A field trail was conducted at College of Forestry, Kerala Agricultural University, (India) with an objective to find out the nutrient content, decomposition pattern and soil improvement by the addition of leaf litters of Acacia mangium. The experiment was conducted in a home garden and in an open area during south west monsoon and north east monsoon seasons. Entire leaf litter decomposed completely within ten months. Decomposition was faster during north east monsoon season particularly during the initial months. The field condition did not influence the rate of decomposition significantly. Strong negative influence of lignin on the rate of decomposition was evident in all the study situations. Generally, litter collected during the second season registered more content of most of the elements like N, P, K, Ca and S at the time of incorporation into soil. Despite the fluctuations in the nutrient concentrations, absolute amounts of most of the nutrients in both the seasons and field conditions gradually declined as decomposition advanced. A characteristic bimodal pattern of biomass decomposition was observed in all the study situations with a rapid initial phase for a period of three months followed by slow later phase. In general, potassium mineralized faster in most of the cases. Calcium and nitrogen mineralized slowly. The influence of leaf litter decomposition on changes in soil pH was not significant. The addition of leaf litter to soil brought out fluctuations in total nitrogen, available phosphorus and exchangeable potassium contents. Accretion in exchangeable calcium and magnesium in the soil was evident at the end of the study. However, the availability of sulphur declined slightly after ten months of incorporation of litters in the soil.